The Influence Of Work-Life Balance On Employee Satisfaction And Performance In Banks (Case Study Of Bsi Kcp Medan Adam Malik) - Lubis, Balqis Mawaddah; Harahap, Muhammad Ikhsan; Anggraini, Tuti (UNIVERSITAS PAKUAN, 2024)
Human resources are resources that play an important role in achieving company goals. Good human resource management will have a positive impact on the company concerned. This research was conducted to determine the effect of Work- Life Balance on job satisfaction and employee performance at Bank BSI KCP Medan Adam Malik. This type of research is explanatory research, which focuses on explaining the relationship between variables, namely the independent variable, namely work-life balance (X), the dependent variable, namely job satisfaction (Y1) and employee performance (Y2). The respondents in this research were all 36 employees of Bank BSI KCP Medan Adam Malik. The data collection method was carried out through distributing questionnaires as a primary source and literature study as a secondary source. Based on the research results, it can be concluded that work-life balance has a significant effect on job satisfaction and work-life balance has an effect on the performance of Bank BSI KCP Medan Adam Malik employees. Apart from that, work-life balance influences employee performance through job satisfaction of Bank BSI KCP Medan Adam Malik employees.